Math Product Law of Radicals. Answer the questions with solutions and accurate answers. 3 1. Can the Product Law of Radicals be applied in simplifying √3*√3? Why or why not? Solution/Explanation: No, since they have different radicals. i.e, cube root and square root. But we can use the law of exponent to calculate such expressions. We know that ax ay =ax+y . In this case, 3 1 3 5 1 √3*√3 = (3)3 (3)2 √3*√3 = (3)6 3 6 √3*√3=√243 2. Explain why √-16*√-4=√64=8 is an incorrect application of the Product Law of Radicals. Solution/Explanation: The above operation is incorrect since a negative square root will result to imaginary numbers. Hence, the proper implementation would be √-16*√-4=(4i)(2i) √-16*√-4=8i2 √-16*√-4=8(-1) √-16*√-4=-8 3. Why do you think that √52 =5 Solution/Explanation: No, this expression is incomplete. Since the square of negative 5 must be included. Hence, the correct expression would be √52 =|5|